Analisis Faktor Yang Mempengaruhi Pengambilan Keputusan Pembelian Produk Scarlett Whitening Melalui Peran Influencer Marketing - Mutiara, Arla Triza; Sukoco, Iwan; Barkah, Cecep Saaftul; Novel, Nurillah Jamil Achmawati (Master of Management Diponegoro University, 2023)
This research analyzes the decision-making process regarding the purchase of ScarlettWhitening skincare products through the role of influencer marketing. The researchutilized the Systematic Literature Review approach for its investigation. After conductingthe systematic literature review, the researchers discovered a total of 78 articles througha search conducted on Google Scholar. Subsequently, these articles were narroweddown to a final selection of 23 for descriptive analysis. The findings indicate that thefactors influencing the success of influencer marketing in influencing the purchasedecision of Scarlett Whitening products are trustworthiness, expertise, attractiveness,similarity, liking, and respect. The results of this study are expected to be considered byScarlett Whitening company in selecting influencers who align with these factors toencourage consumers to decide to purchase the product.